Monitoring Suhu Ruang Server Di PT. TIKI Tangerang - Adi Prasetyo; Natanael Natanael; Essa Purnama Aji (CICES (Cyberpreneurship Innovative and Creative Exact and Social Science), 2017)
Computer/laptop is an electronic device that is commonly used as a tool to do all the activities that can assist humans in many different areas of business, besides in its use should be cared for properly, PT TIKI Tangerang does not yet have the server so that the room temperature with the progress of science and technology in particular in the field of mikrokontroller then it can be created server room temperature monitoring system based arduino , by utilizing the workings of LM35 temperature sensor then can be made of temperature monitor system for the performance of the server space. By utilizing a lcd display 16x2 then the temperature of the processor can be shown on the display screen in theform of characters in the form of analogue to digital conversion. And by utilizing the local website then the results the LM35 temperature sensor detection tesimpan into the database can be seen wherever and whenever. LM35 temperature sensor readings are processed mikrokontroller jawani arduino, and data results from the process will be shown to the lcd display. the system can display the temperature at any moment in time one time per second. And by utilizing the W5100 ethernet shield then the tesimpan detection results into the database can be viewed on the website of the local.